Development of a Narrative Writing Skills Assessment Rubric through Differentiated Instruction for Junior Secondary School - Khotimah, Husnul; Ninuk Lustyantie , Ninuk Lustyantie; Fathiaty Murtadho, Fathiaty Murtadho (Universitas Negeri Padang, 2025)
The development of a narrative writing assessment rubric based on differentiated instruction serves as a solution to the need for an evaluation instrument that is responsive to the diversity of junior high school students. Using the Research and Development (R&D) approach by Borg & Gall, the rubric was designed with five assessment dimensions and validated by experts. Reliability testing was conducted using Cohen’s Kappa, and its effectiveness was examined through a paired t-test. The results showed a significant improvement in the quality of students’ writing, particularly in text structure and grammar. Questionnaire and interview data further confirmed that the rubric provided clarity in assessment and increased student motivation and participation. Teachers found the rubric helpful for conducting objective and consistent evaluations. This rubric supports the implementation of the Kurikulum Merdeka, which emphasizes an inclusive and differentiated instructional approach. Keywords: Assessment Rubric, Narrative Writing, Differentiated Instruction, Kurikulum Merdeka, Junior Secondary School